HIV Tat-Mediated Induction of Monocyte Transmigration Across the Blood–Brain Barrier: Role of Chemokine Receptor CXCR3 - Niu, Fang; Liao, Ke; Hu, Guoku; Moidunny, Shamsudheen; Roy, Sabita; Buch, Shilpa (Frontiers in Cell and Developmental Biology, 2021)
HIV Trans-Activator of Transcription (Tat), one of the cytotoxic proteins secreted from HIV-infected cells, is also known to facilitate chemokine-mediated transmigration of monocytes into the brain leading, in turn, to neuroinflammation and thereby contributing to the development of HIV-associated neurocognitive disorders (HAND). The mechanism(s) underlying HIV Tat-mediated enhancement of monocyte transmigration, however, remain largely unknown. CXC chemokine receptor 3 (CXCR3) that is expressed by the peripheral monocytes is known to play a role in the monocyte influx and accumulation. In the present study, we demonstrate for the first time that exposure of human monocytes to HIV Tat protein resulted in up-regulated expression of CXCR3 leading, in turn, to increased monocyte transmigration across the blood-brain barrier (BBB) both in the in vitro and in vivo model systems. This process involved activation of toll like receptor 4 (TLR4), with downstream phosphorylation and activation of TANK-binding kinase 1 (TBK1), and subsequent phosphorylation and nuclear translocation of Interferon Regulatory Factor 3 (IRF3), ultimately leading to enhanced expression of CXCR3 in human monocytes. These findings imply a novel molecular mechanism underlying Tat-mediated increase of monocyte transmigration across the BBB, while also implicating a novel role of CXCR3-dependent monocyte transmigration in HIV Tat-mediated neuroinflammation.